Rapid and Accurate Detection of SARS Coronavirus 2 by Nanopore Amplicon Sequencing - Li, Xiao-xiao; Li, Chao; Du, Peng-cheng; Li, Shao-yun; Yu, Le; Zhao, Zhi-qiang; Liu, Ting-ting; Zhang, Cong-kai; Zhang, Sen-chao; Zhuang, Yu; Dong, Chao-ran; Ge, Qing-gang (Frontiers in Microbiology, 2022)
Objective: To evaluate the performance of nanopore amplicon sequencing detection for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in clinical samples. Method: We carried out a single-center, prospective cohort study in a Wuhan hospital, and collected a total of 86 clinical samples, including 54 pharyngeal swabs, 31 sputum samples and 1 fecal sample, from 86 patients with coronavirus disease 2019 (COVID-19) from Feb 20th to May 15th, 2020. We performed parallel detection of nanopore based genome amplification and sequencing (NAS) on an ONT minION platform and routine RT-qPCR. In addition, 27 negative control samples were detected using the two methods. The sensitivity and specificity of NAS were evaluated and compared with those of reverse transcription quantitative polymerase chain reaction (RT-qPCR). Results: The viral read number and reference genome coverage were both significant different between the two groups of samples, and the latter one was a better indicator for SARS-CoV-2 detection. Based on reference genome coverage, NAS revealed both high sensitivity (96.5%) and specificity (100%) compared with RT-qPCR (80.2% and 96.3%), although the samples have been stored for half a year before the detection. The total time cost was less than 15 hours, which was acceptable compared with that of RT-qPCR (~2.5 hours). In addition, the reference genome coverage of the viral reads was in line with the cycle threshold value of RT-qPCR, indicating that this number could also be used as an indicator of the viral load in sample. The viral load in sputum might be related with the severity of the infection particularly in patients within 4 weeks after first shown clinical manifestations, which could be used to evaluate the infection. Conclusion: Our results showed high sensitivity and specificity of NAS SARS-CoV-2 detection method compared with RT-qPCR. The sequencing results were also used as indicator of viral load to display the viral dynamics during infection. This study proved the wide application prospect of nanopore sequencing detection on SAR-CoV-2 and more knowledge about the clinical characteristics of COVID-19.